The Effect of Work Atmosphere and Job Training on Employee Retention: A Test of Multigroup Moderated Mediation Effect - Natasya Putri Salsabilla; Vivin Maharani Ekowati (Jurnal Ecogen, 2025)
This research evaluates how the work atmosphere and job training influence employee retention in the restaurant sector in Malang City, with job satisfaction as a mediator and intrinsic motivation as a moderator. Adopting a quantitative explanatory design, the study employs the SEM-PLS analysis technique via SmartPLS 4. Primary data were gathered through questionnaires distributed to 149 employees chosen using a proportional stratified random sampling method. The findings indicate that the work atmosphere does not significantly affect employee retention, whereas job training does. Furthermore, job satisfaction serves as a mediator linking both work atmosphere and training to employee retention. Conversely, intrinsic motivation did not moderate the relationship between training and retention. Consequently, the study highlights the need to foster a supportive work environment, implement practical training, and boost job satisfaction to enhance staff retention in the restaurant service industry.